Admixture patterns and genetic differentiation in negrito groups from West Malaysia estimated from genome-wide SNP data - Timothy Adrian, Jinam; Maude E., Phipps; Naruya, Saitou (Wayne State University Press, 2013)
Southeast Asia houses various culturally and linguistically diverse ethnic groups. In Malaysia, where the Malay, Chinese, and Indian ethnic groups form the majority, there exist minority groups such as the "negritos" who are believed to be descendants of the earliest settlers of Southeast Asia. Here we report patterns of genetic substructure and admixture in two Malaysian negrito populations ( Jehai and Kensiu), using ~50,000 genomewide single-nucleotide polymorphism (SNP) data. We found traces of recent admixture in both the negrito populations, particularly in the Jehai, with the Malay through principal component analysis and STRUCTURE analysis software, which suggested that the admixture was as recent as one generation ago. We also identified significantly differentiated nonsynonymous SNPs and haplotype blocks related to intracellular transport, metabolic processes, and detection of stimulus. These results highlight the different levels of admixture experienced by the two Malaysian negritos. Delineating admixture and differentiated genomic regions should be of importance in designing and interpretation of molecular anthropology and disease association studies.